Varicella zoster virus–infected cerebrovascular cells produce a proinflammatory environment. Issue 5 (September 2017) - Jones, Dallas; Neff, C. Preston; Palmer, Brent E.; Stenmark, Kurt; Nagel, Maria A.
Abstract : Objective: To test whether varicella zoster virus (VZV) infection of human brain vascular cells and of lung fibroblasts directly increases proinflammatory cytokine levels, consistent with VZV as a causative agent in intracerebral VZV vasculopathy and giant-cell arteritis (GCA). Methods: Conditioned supernatant from mock- and VZV-infected human brain vascular adventitial fibroblasts (HBVAFs), human perineurial cells (HPNCs), human brain vascular smooth muscle cells (HBVSMCs), and human fetal lung fibroblasts (HFLs) were collected at 72 hours postinfection and analyzed for levels of 30 proinflammatory cytokines using the Meso Scale Discovery Multiplex ELISA platform. Results: Compared with mock infection, VZV infection led to significantly increased levels of the following: interleukin-8 (IL-8) in all cell lines examined; IL-6 in HBVAFs, HPNCs, and HFLs, with no change in HBVSMCs; and vascular endothelial growth factor A in HBVAFs, HBVSMCs, and HFLs, with a significant decrease in HPNCs. Other cytokines, including IL-2, IL-4, IL-15, IL-16, TGF-b, Eotaxin-1, Eotaxin-3, IP-10, MCP-1, and granulocyte macrophage colony-stimulating factor, were also significantly altered upon VZV infection in a cell type–specific manner. Conclusions: VZV infection of vascular cells can directly produce a proinflammatory environment that may potentially lead to prolonged arterial wall inflammation and vasculitis. The VZV-mediated increase in IL-8 and IL-6 is consistent with that seen in the CSF of patients with intracerebral VZV vasculopathy, and the VZV-mediated increase in IL-6 is consistent with the cytokine's elevated levels in temporal arteries and plasma of patients with GCA.